Analisis Pengaruh Pengungkapan Corporate Sosial Responsibility Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Varabel Moderasi (Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Nur Oktavia Andriyani; Aida Nahar (Jurnal Rekognisi Akuntansi, 2020)
This research stems from the problem of the lack of attention of a number of companies on corporate social responsibility so that the purpose of this study is to determine whether Corporate Social Responsibility has an effect on firm value with profitability as a moderating variable in mining companies listed on the Stock Exchange for the 2016-2019 period. This study uses descriptive statistical data analysis techniques, classical assumption test, multiple linear regression, R2 test, F test, and T test. The sample of this research is the disclosure of corporate social responsibility through annual reports in the mining sector for the 2016-2019 period using the sampling method. Fed up. There are 64 companies listed on the IDX for the 2016-2019 period. By using saturated sampling, the entire population was sampled, so that the sample in this study was 64 companies. Based on the results of research conducted using the Statistical Product and Service Solution (SPSS 20), it shows that corporate social responsibility has an effect on firm value and profitability is able to strengthen the influence of corporate social responsibility on firm value, it is known that the t-count value is smaller than the t-table value, and the significance value is greater than the level of significance. Simultaneously or simultaneously, the independent variables of corporate social responsibility and profitability as moderating influence on the dependent variable, namely firm value.